2010
DOI: 10.1007/s11130-010-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Capacity and Phenol Content in Jackfruit (Artocarpus heterophyllus Lam.) Fruit Pulp

Abstract: The antioxidant capacity of jackfruit (Artocarpus heterophyllus Lam. Fam. Moracae) fruit pulp (JFP) obtained from Western Ghats India was determined by evaluating the scavenging activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing power assays and N, N-dimethyl-p-phenylendiamine (DMPD) radical cation decolorization assay. JFP was analyzed for total phenolic content (TPC) and total flavonoids content (TFC). The ethanol and water are the best solvents for the extracting phenols and flavonoids fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
4
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 23 publications
12
83
4
5
Order By: Relevance
“…A. heterophylus exhibited significant antioxidant activity studied its pulp presenting antioxidant capacity against DPPH radical, ferric reducing power and radical DMPD was studied. The jackfruit is a rich source of phytochemicals including phenolic compounds and offers opportunities for development of value-added products from jackfruit (Jagtap et al, 2010).…”
Section: Total Phenolic Compounds (Tpc)mentioning
confidence: 99%
“…A. heterophylus exhibited significant antioxidant activity studied its pulp presenting antioxidant capacity against DPPH radical, ferric reducing power and radical DMPD was studied. The jackfruit is a rich source of phytochemicals including phenolic compounds and offers opportunities for development of value-added products from jackfruit (Jagtap et al, 2010).…”
Section: Total Phenolic Compounds (Tpc)mentioning
confidence: 99%
“…But this does not corroborate with the findings of Soong and Barlow (2004) who reported that seeds of jackfruit showed higher amounts of total phenolics content (27.7 mg GAE g −1 ). It is reported that ethanol extract of jackfruit pulp resulted in total phenolics content of 0.46 mg GAE g −1 (Jagtap et al 2010). These differences in total phenolics of same fruits may be due to the complexity of these compounds and the methods of extraction and analysis (Kalt et al 2001).…”
Section: Total Polyphenolsmentioning
confidence: 99%
“…Jackfruit pulp and grape pulp extracts were found to have significantly lower flavonoids (0.11 and 0.23 mg CE g −1 respectively) as compared to the others. Jagtap et al (2010) reported that the water extract of jackfruit pulp showed more flavonoid content (1.20 mg of rutin equivalents g −1 ). The flavonoids content of whole mulberry fruit extract was 4.01 mg CE g −1 which was significantly higher than jamun pulp, jackfruit pulp, jackfruit seed, grape skin and grape pulp extracts.…”
Section: Total Flavonoidsmentioning
confidence: 99%
“…Previous studies have examined the free sugar distribution and compositions of fatty acids (Chowdhury, Raman, & Mian, 1997), carbohydrates (Rahman, Nahar, Jabbar, & Mosihuzzaman, 1999), aroma volatiles (Swords, Bobbio, & Hunter, 1978;Rasmussen, 1983;K. Wong, Lim, & L. Wong, 1992;Maia, Andrade, & Zoghbi, 2004), carotenoids and phenolics (Chandrika, Jansz, & Warnasuriya, 2005;Jayasinghe, Rupasinghe, Hara, & Fujimoto, 2006;Faria, Rosso, & Mercadante, 2009) from fruits of different jackfruit varieties, as well as antioxidant capacity and phenol content in jackfruit fruit pulp (Jagtap, Panaskar, & Bapat, 2010). For example, an early study found little changes in fruit total acidity during ripening (Bhatia, Siddapa, & Lal, 1955).…”
Section: Introductionmentioning
confidence: 99%